The barriers and facilitators to routine outcome measurement by allied health professionals in practice: a systematic review - Duncan Edward AS; Murray Jennifer (BMC, 2012)
Abstract Background Allied Health Professionals today are required, more than ever before, to demonstrate their impact. However, despite at least 20 years of expectation, many services fail to deliver routine outcome measurement in practice. This systematic review investigates what helps and hinders routine outcome measurement of allied health professionals practice. Methods A systematic review protocol was developed comprising: a defined search strategy for PsycINFO, MEDLINE and CINHAL databases and inclusion criteria and systematic procedures for data extraction and quality appraisal. Studies were included if they were published in English and investigated facilitators and/or barriers to routine outcome measurement by allied health professionals. No restrictions were placed on publication type, design, country, or year of publication. Reference lists of included publications were searched to identify additional papers. Descriptive methods were used to synthesise the findings. Results 960 papers were retrieved; 15 met the inclusion criteria. Professional groups represented were Physiotherapy, Occupational Therapy, and Speech and Language Therapy. The included literature varied in quality and design. Facilitators and barriers to routine outcome measurement exist at individual, managerial and organisational levels. Key factors affecting professionals' use of routine outcome measurement include: professionals' level of knowledge and confidence about using outcome measures, and the degree of organisational and peer-support professionals received with a view to promoting their work in practice. Conclusions Whilst the importance of routinely measuring outcomes within the allied health professions is well recognised, it has largely failed to be delivered in practice. Factors that influence clinicians' ability and desire to undertake routine outcome measurement are bi-directional: they can act as either facilitators or barriers. Routine outcome measurement may only be deliverable if appropriate action is taken at individual therapist, team, and organisational levels of an organisation.